1987
DOI: 10.1111/j.1526-4610.1987.hed2707372.x
|View full text |Cite
|
Sign up to set email alerts
|

Atenolol in Migraine Prophylaxis a Double‐blind Cross‐over Multicentre Study

Abstract: SYNOPSIS The prophylactic anti‐migraine effect of atenolol was compared to placebo in a multicentre study on 63 patients with classical and/or common migraine. The study design was double‐blind cross‐over and patients were given atenolol 100 mg o.d. or matching placebo during a study treatment period of 24 weeks. The effect of atenolol was significantly better than that of placebo: integrated headache values were reduced in 70% of the patients (p = 0.004) and the proportion of days with headache was reduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 8 publications
1
17
0
6
Order By: Relevance
“…While propranolol, metoprolol, oxprenolol, and alprenolol are very lipophilic and, hence, penetrate well into the central nervous system, atenolol, nadolol, and practolol are only slightly or not at all lipophilic (Cruickshank and Prichard 1994). As several members of the latter group, including atenolol (Forssman et al 1983;Johannsson et al 1987) and nadolol (Freitag and Diamond 1984;Sudilovsky et al 1987), have been reported to be effective in the prophylactic treatment of migraine attacks, high lipophilicity and, hence, penetration into the central nervous system does not appear to be required for prophylactic efficacy. The reports on prophylactic efficacy of atenolol (Forssman et al 1983;Johannsson et al 1987), nadolol (Freitag and Diamond 1984;Sudilovsky et al 1987), and timolol (Stellar et al 1984;Tfelt-Hansen et al 1984) suggest that membrane-stabilizing effects are not required to reduce the frequency of migraine attacks.…”
Section: β-Adrenoceptorsmentioning
confidence: 99%
“…While propranolol, metoprolol, oxprenolol, and alprenolol are very lipophilic and, hence, penetrate well into the central nervous system, atenolol, nadolol, and practolol are only slightly or not at all lipophilic (Cruickshank and Prichard 1994). As several members of the latter group, including atenolol (Forssman et al 1983;Johannsson et al 1987) and nadolol (Freitag and Diamond 1984;Sudilovsky et al 1987), have been reported to be effective in the prophylactic treatment of migraine attacks, high lipophilicity and, hence, penetration into the central nervous system does not appear to be required for prophylactic efficacy. The reports on prophylactic efficacy of atenolol (Forssman et al 1983;Johannsson et al 1987), nadolol (Freitag and Diamond 1984;Sudilovsky et al 1987), and timolol (Stellar et al 1984;Tfelt-Hansen et al 1984) suggest that membrane-stabilizing effects are not required to reduce the frequency of migraine attacks.…”
Section: β-Adrenoceptorsmentioning
confidence: 99%
“…Interestingly, the intake of ergotamine products was significantly lower in all patients using such drugs. (Johannsson et al 1987) also confirmed that the effect of atenolol 100 mg o.d. is significantly better than that of placebo.…”
Section: Introductionmentioning
confidence: 79%
“…С целью профилактики мигрени используют -блокаторы, антиконвульсанты, антидепрессанты и другие лекарственные средства [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Пропранолол в дозе от 40 до 120 мг 2 раза в сутки, метопролол в дозе 25-100 мг 2 раза в сутки рекомендованы в качестве терапии первой линии для профилактики мигрени.…”
Section: профилактика мигрениunclassified